PENERAPAN METODE VALUE FOR MONEY SEBAGAI TOLOK UKUR PENILAIAN KINERJA KEUANGAN PADA ORGANISASI SEKTOR PUBLIK DI DINAS KESEHATAN KOTA MANADO - Wuwungan, Gabriela Thalia; Tinangon, Jantje; Rondonuwu, Sintje (GOING CONCERN : JURNAL RISET AKUNTANSI, 2019)
In this era of globalization, many people consider the financial sector of public sector organizations as a waste and a source of funding. Loss of public trust in lost public sector organizations. In addition, accountability reports on public sector organizations are only oriented to "output" rather than "outcome". This discusses the phenomenon that public sector organizations pay more attention to the value of money that can be considered inputs, outputs, before the results that underlie the three main elements namely economy, efficiency and effectiveness. Research in the city of Manado using the value for money method, in terms of economy, efficiency and effectiveness. The analytical method used in this thesis research using descriptive qualitative methods, namely the results of interviews and with the data collected were analyzed and conclusions were collected. The results of the research obtained from the research results of the Manado City Health Office obtained the value for money method for economic measurement and efficiency, achieving good results. However, to measure success is still not good, decided one of the programs carried out has not been approved. Manado City Health Office should pay more attention to the results of the community in each program that is carried out, so that it is easier to find out which programs meet the requirements or not.